Pengaruh Pendidikan-Latihan Keselamatan Kerja, Pengalaman Kerja, Dukungan Manajerial dan Pangkat terhadap Sikap Pekerja Industri Berpendidikan Rendah - Djoko Kustono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This study was intended to examine whether safety-training, working experience, working position and managerial support influence in the workers' attitudes toward safety priority. The population were low level education workers in East Jawa industries. It was found that safety-training, working experience, working position and managerial support significantly influence in their attitudes toward safety priority. The contribution of all predictors were 47.7 %. Individually, safety training and working experience significantly contribute to the attitudes. While safety training shared 29.4 % and working experience shared 9.4 %, the contribution of working position and managerial supports were not significant.